Circulatory and Metabolic Physiology Disorder in Different Organs of the Subtropical Scallop Species Chlamys nobilis Under Thermal and Hypoxia Stress, Revealed by Doppler Ultrasonography Technique - Hao, Yu; Sun, Chunyang; Rong, Yun; Wang, Haiqing; Xu, Qiang; Gao, Fei; Wang, Aimin (Frontiers in Marine Science, 2022)
Extremely high temperature and hypoxia are mounting problems affecting the world’s coastal waters under the global warming environment, with severe consequences for marine life. Scallop is one of the most fragile species to hypoxia stress for their high respiration rate and lack of self-protection ability such as long-time shell closing. Circulatory physiology rhythm is sensitive to environmental stress and is an important means for shellfish to quickly respond to environmental stress. Therefore, monitoring the circulatory physiology indexes of Chlamys nobilis under hypoxia and high temperature stress is helpful to quickly diagnose its stress state and reveal the response process of circulatory system to the stress. In this study, using real-time Doppler ultrasonography technique, we continuously monitored the circulatory physiological indexes [heart rate (HR), blood flow volume (FV), blood velocity (PS and ED), resistance index (RI) and S/D ratio) of the scallop organs (gill, mantle and adductor muscle) under hypoxia (mild 4 mg/L DO, moderate 3 mg/L DO and severe 2 mg/L DO)] and fluctuating high temperature stress (29-31°C). Important metabolic function indexes [adenosine triphosphate (ATP), pyruvate kinase (PK) and cytochrome C oxidase (COX)] of various tissues were measured simultaneously. The results show that scallops are very sensitive to the changes of temperature and dissolved oxygen. Both high temperature and hypoxia will increase the HR, and severe hypoxia will bring greater load to the heart of the scallop. Hypoxia stress mainly caused the changes of PS, and the RI and S/D of the gill gradually increased. At 2mg/L DO level, the total blood flow of the mantle and adductor muscle decreased, but the blood flow supply in the gill was stable. The scallop is very sensitive to the change of high temperature and can make adjustments immediately. High temperature increased blood flow in various organs and preferentially supplied to the gill. The RI and S/D of branchial vessels under high temperature were lower than those under hypoxia. The ATP content of the mantle was continuous accumulated under high temperature and was significantly higher than that of the gill and adductor muscle, indicating the specificity of tissue metabolism. The overall circulatory physiological indexes of the gill showed a more positive response to the stress environment than the mantle and adductor muscle. All the results proved that the gill has the best resistance to the hypoxia and high temperature stress. Our study revealed the circulatory physiology regulation mechanism of the noble scallop C. nobilis under environmental stress, and provide effective data and technique supports for the timely diagnose of stress condition of the species, so as to formulate necessary handling strategies for the scallop farm.